[OA044] Quantitative DW-MRI for treatment evaluation in particle therapy: ROLE of ADC maps estimation. (August 2018) - Buizza, Giulia; Paganelli, Chiara; Fontana, Giulia; Franconeri, Andrea; Raciti, Maria Vittoria; Viselner, Gisela; Anemoni, Luca; Iannalfi, Alberto; Preda, Lorenzo; Baroni, Guido
Abstract : Purpose: Apparent diffusion coefficient (ADC) plays a key-role in the context of quantitative diffusion-weighted MRI (DW-MRI) for response assessment in particle-therapy. With this purpose, threshold values defined on ADC could be clinically used to discriminate respondent and not-respondent patients. However, concordant ADC measurements are required for their acceptance as quantitative biomarkers[1] . This study aims at retrospectively investigating the role of ADC maps estimation by comparing different offline strategies with respect to an online map, directly derived from the clinical scanner. Methods: DW-MRI at 7 b-values (0, 50, 100, 150, 200, 400, 1000 s/mm 2 ) were acquired during 58 examinations of the brain using a clinical MR scanner (3T). ADC was computed online and offline. For the latter case, DW-MR images at two (ADC_2b: 0–1000 s/mm 2 ; ADC_200b: 200–1000 s/mm 2 ), three (ADC_3b: 50-400–1000 s/mm 2 ) and all (ADC_7b) b-values were used to linearly fit a mono-exponential model exploiting least-square optimization. Voxel-wise absolute differences were computed between any offline and the online ADC for each exam (ΔADC_∗∗b), both on the whole image and on the manually delineated gross tumour volume (GTV). Median values of such differences were then compared using the Friedman test ( α = 0.01). Results: Evaluating the whole DW-MRI images, ΔADC_2b did not show any statically significant difference with respect to ΔADC_3b, whereas all other pairs did. Focusing on the GTV, differences between any pair were found to be significantly different. The smallest differences were found for ΔADC_7b ( median WHOLE [iqr] = 0.011 [0.009] and median GTV [iqr] = 0.006 [0.001] 10 - 3 mm 2 /s) and the highest for Δ ADC_200b ( median WHOLE [iqr] = 0.274 [0.034] and median GTV [iqr] = 0.231 [0.034] 10 - 3 mm 2 /s), whereas Δ ADC_3b and Δ ADC_2b showed intermediate results. Conclusions: From this preliminary evaluation, online ADC seems to make use of all available DW images, thus better relating to ADC_7b. Attention must be paid when comparing discriminative threshold values based on online ADC maps and studies aiming at defining the optimal b-values combination for different target tissues should be encouraged.